1987
DOI: 10.1002/j.1460-2075.1987.tb02686.x
|View full text |Cite
|
Sign up to set email alerts
|

5′ Analysis of the soybean leghaemoglobin lbc 3 gene: regulatory elements required for promoter activity and organ specificity

Abstract: The soybean leghaemoglobin lbc3 gene promoter was analysed in transgenic Lotus corniculatus plants. Hybrid‐promoter constructions and 5′ deletions were studied using chimeric genes composed of the various promoters, the chloramphenicol acetyltransferase (CAT) coding sequence and the lbc3 3′ flanking region. A 5′ Bal31 deletion series mapped a strong positive regulatory element between −1100 and −950. A weaker element located between −230 and −170 defined the minimum 5′ region required for detectable promoter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
129
0

Year Published

1988
1988
2006
2006

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 152 publications
(132 citation statements)
references
References 26 publications
3
129
0
Order By: Relevance
“…However, the sequence content of two adjacent 14-and 12-nucleotide blocks located between position Ϫ384 and Ϫ352 of the LjNin promoter and between Ϫ385 and Ϫ352 of the PsNin promoter attracts attention. The proximal 14-nucleotide-long conserved sequence is a perfect match to the 3Ј half (TTGTCTCTT) of the extended organ-specific element (AAAGATNNTT-GTCTCTT) first identified in the soybean and Sesbania rostrata leghemoglobin promoters and subsequently found in other nodule expressed genes (Stougaard et al, 1987;Ramlov et al, 1993;Szczyglowski et al, 1994). Interestingly, the same sequence encompasses a TGTCTC sequence shown in Arabidopsis to be an auxin-responsive element binding the ARF1 transcription factor (Ulmasov et al, 1997).…”
Section: Analysis Of Expression Of Psninmentioning
confidence: 93%
“…However, the sequence content of two adjacent 14-and 12-nucleotide blocks located between position Ϫ384 and Ϫ352 of the LjNin promoter and between Ϫ385 and Ϫ352 of the PsNin promoter attracts attention. The proximal 14-nucleotide-long conserved sequence is a perfect match to the 3Ј half (TTGTCTCTT) of the extended organ-specific element (AAAGATNNTT-GTCTCTT) first identified in the soybean and Sesbania rostrata leghemoglobin promoters and subsequently found in other nodule expressed genes (Stougaard et al, 1987;Ramlov et al, 1993;Szczyglowski et al, 1994). Interestingly, the same sequence encompasses a TGTCTC sequence shown in Arabidopsis to be an auxin-responsive element binding the ARF1 transcription factor (Ulmasov et al, 1997).…”
Section: Analysis Of Expression Of Psninmentioning
confidence: 93%
“…1; Fehlberg et al 2005). Thus, although detailed promoter studies in AM roots are obviously far from comprehensive, it emerges that the situation is more complex than in the root nodule symbiosis where organspecific-elements (OSEs) were reported to be sufficient to direct gene expression to the infected cells of root nodules (Stougaard et al 1987).…”
Section: Towards a Molecular Basis Of Gene Expression Regulation In Amentioning
confidence: 99%
“…A less conserved AAAGAT-like motif was identified at an analogous position in the promoter region of Ib genes from M. A comparison of the DNA sequences in the 5' upstream regions of (1eg)hemoglobin genes from S. rostrata (Metz et al, 1988). soybean (lba, lbcl, lbc2, and lbc3; Stougaard et al, 1987), pea (pslb; Nap, 1988), M. truncatula (Mtlbl and MtlbP;Gallusci et al, 1991), M. sativa (Msl and Msplb2;Davidowitz et al, 1991), T: tomentosa (Tmma; Bogusz et ai., 1990), and I ? andersonii(far8; Bogusz et al, 1990) is shown.…”
Section: The Nlce Element Contains Highly Consewed Dna Motlfsmentioning
confidence: 99%
“…In the equivalent region of the soybean lbc3 promoter, two important elements have been identified: an OSE (-139 to -102) relative to the start point of transcription, which is required but not sufficient for nodule-specific expression, and an NE (-102 to -49), which is apparently involved in repression of lbc3 promoter activity (Stougaard et al, 1987(Stougaard et al, ,1990. Together, OSE and NE were found to be able to confer a nodule-specific (enhanced) pattern of gene expression on the CaMV 35s promoter in transgenic L. corniculatus plants (Lauridsen et al, 1991).…”
Section: Dlscusslonmentioning
confidence: 99%
See 1 more Smart Citation